2016
DOI: 10.1177/2054270416629326
|View full text |Cite
|
Sign up to set email alerts
|

Rare times rare: The hyponatremia, rhabdomyolysis, anterior compartment syndrome sequence

Abstract: LessonPrimary polydipsia occurs in up to 25% of patients with chronic psychiatric disorders (especially schizophrenia), related to the disease, its treatment or both. Urine output fails to match intake >10 L/day and water intoxication may develop. Rhabdomyolysis is a rare complication of hyponatremia, and an acute anterior compartment syndrome of the leg, an emergency, may be very rarely associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our findings are consistent with two previous observational studies suggesting rapid serum sodium correction is associated with rhabdomyolysis [ 7 , 8 ]. In addition, although rhabdomyolysis is a rare complication of hyponatremia according to previous case reports, rhabdomyolysis would be an under-recognized complication based on our results [ 5 , 12 ]. Previous studies have suggested that the incidence of rhabdomyolysis in water intoxication patients is approximately 30 to 55% [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 55%
“…Our findings are consistent with two previous observational studies suggesting rapid serum sodium correction is associated with rhabdomyolysis [ 7 , 8 ]. In addition, although rhabdomyolysis is a rare complication of hyponatremia according to previous case reports, rhabdomyolysis would be an under-recognized complication based on our results [ 5 , 12 ]. Previous studies have suggested that the incidence of rhabdomyolysis in water intoxication patients is approximately 30 to 55% [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 55%
“…Compartment syndrome isolated to the anterior compartment and from a medically induced aetiology is very rare. Our review found only five published cases [1][2][3][4][5]. Four cases were secondary to psychogenic polydipsia, and one case attributed to severe primary hypothyroidism and adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 92%
“…All of the published cases similar to the one described in this case report resulted in permanent disability due to delays in recognising the diagnosis. Drop foot and loss of sensation in the dorsal foot is the likely outcome for a patient with delayed release of the anterior compartment [1,3,4]. This is due to necrosis of the muscles in the anterior compartment and/or compression of the deep peroneal nerve as it passes through the compartment, supplying the muscles before giving sensation to the 1st webspace on the dorsum of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…There are many causes of hypotonic hyponatremia: primary polydipsia, syndrome of inappropriate antidiuretic hormone secretion (SIADH), renal failure, adrenal insufficiency, and heart failure. To differentiate between these causes, volume status, urine sodium, and urine osmolality need to be assessed [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%